Capulin Photographs
Collection of Black and White Photographs of Capulin Volcano
Master list item #: 1
File located in the Raton Filing Cabinet
Keywords: Capulin Volcano; Landscapes; Volcanos; Landmarks; State Parks; Capulin, New Mexico